Social Outbreak, Politics and Democracy [Estallido Social, Política y Democracia] - Friz-Echeverria, C (Universidad de Talca, 2021)
The conjuncture in which we are from October to date has been predominantly interpreted as a social crisis; this is accounted for "social outbreak" expression. It is worth asking, on the one hand, the understanding of the crisis that is supposed in this social elaboration. On the other hand, it is worth asking about the possibilities of overcoming the crisis that such an emphasis on the social implies. Trying to answer these questions, we will ask, first of all, about limits that separate and unite the social and politics. In a second moment, we will propose that the current crisis has been interpreted as a social phenomenon, since the generalized understanding in Chile negatively perceives politics as excess, as a terrain of conflict that leads to violent and abrupt breakdowns. Finally, we will propose that the current crisis should be assumed as a political and democratic phenomenon. This depends, in our interpretation, on a reconceptualization of politics and democracy, which takes account the positive potentials of conflicts exposed during the last months. © 2021 Universidad de Talca. All right reserved.